How not to read Plato - Xavier, Dennys Garcia (Revista Archai, 2011)
In this article, we establish a general picture about the historical-philosophical origins of the hermeneutical path of interpretation of Plato’s works which was inaugurated by F. Schleiermacher in the early 19th century. Some of its compositional characteristics - which can be found in the work of many important scholars of different schools and historical moments ”“ are explored, and arguments are given as to their evident insufficiency for understanding Plato’s Works.